Two Birds, One Stone: Double Hits on Tumor Growth and Lymphangiogenesis by Targeting Vascular Endothelial Growth Factor Receptor 3 - Ming-Chuan Hsu (Cells, 2019)
Vascular endothelial growth factor receptor 3 (VEGFR3) has been known for its involvement in tumor-associated lymphangiogenesis and lymphatic metastasis. The VEGFR3 signaling is stimulated by its main cognate ligand, vascular endothelial growth factor C (VEGF-C), which in turn promotes tumor progression. Activation of VEGF-C/VEGFR3 signaling in lymphatic endothelial cells (LECs) was shown to enhance the proliferation of LECs and the formation of lymphatic vessels, leading to increased lymphatic metastasis of tumor cells. In the past decade, the expression and pathological roles of VEGFR3 in tumor cells have been described. Moreover, the VEGF-C/VEGFR3 axis has been implicated in regulating immune tolerance and suppression. Therefore, the inhibition of the VEGF-C/VEGFR3 axis has emerged as an important therapeutic strategy for the treatment of cancer. In this review, we discuss the current findings related to VEGF-C/VEGFR3 signaling in cancer progression and recent advances in the development of therapeutic drugs targeting VEGF-C/VEGFR3.